2017
DOI: 10.1016/j.athoracsur.2016.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Open Surgical Repair Remains the Gold Standard for Treating Aortic Arch Pathology

Abstract: These results set a standard against which endovascular technology needs to be compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…While traditional open surgery is still considered by some as the gold standard for treatment of extensive aortic arch pathologies (4,5), others have suggested hybrid techniques such as the frozen elephant trunk and aortic arch vessel debranching as more appropriate procedures for high-risk patients, where co-morbidities may contraindicate cardiopulmonary bypass and longer operative times required for traditional repair (6,7). Total-endovascular techniques are also being developed and may soon be a more widely utilized treatment option (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…While traditional open surgery is still considered by some as the gold standard for treatment of extensive aortic arch pathologies (4,5), others have suggested hybrid techniques such as the frozen elephant trunk and aortic arch vessel debranching as more appropriate procedures for high-risk patients, where co-morbidities may contraindicate cardiopulmonary bypass and longer operative times required for traditional repair (6,7). Total-endovascular techniques are also being developed and may soon be a more widely utilized treatment option (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The operative time for TEVAR with ISLF was 252.2 AE 50 min (range: 182-400) with a mean contrast volume of 203.9 AE 37.5 ml (range: 150-300). The length of stay was 7.2 AE 2.1 days (range: [5][6][7][8][9][10][11][12][13][14]. A patient with brachial artery access suffered hematoma and underwent incision repair at the puncture site.…”
Section: Early Resultsmentioning
confidence: 99%
“…The traditional treatment of open total aortic arch replacement is a highly complex procedure that carries a substantial risk of morbidity and mortality . Although novel endovascular techniques that use fenestrations, branches, and parallel stent grafts to incorporate the branches of the aortic arch were recently developed , the application of endovascular repair of the aortic arch remains challenging because it involves one or more aortic arch vessels and appropriate devices are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Would arch vessel reconstruction correlate to development of neurologic dysfunction during the reconstruction? A history of neurologic events, 22 older age, 23 or urgency 24 has been shown to be a significant risk factor for intraoperative neurologic events under SCP. However, a multicenter study investigating brain protection using SCP demonstrated that the duration of cerebral perfusion had no impact on neurologic outcome.…”
Section: Discussionmentioning
confidence: 99%